“ESTABLECER UNA EVALUACIÓN PSICOLÓGICA ADECUADA, PREVIA A DICTAMINAR LA TENENCIA DE LOS MENORES DE EDAD DURANTE EL JUICIO DE DIVORCIO.” - ESPINOSA BRAVO., BAYRON ADRIÁN (2020)
This paper analyzes the granting of the possession of minor children during the divorce proceedings, which requires a thorough analysis of the family as an institution aimed at the protection of its members; The foregoing requires a complementary knowledge of tenure and parental rights as pillars of Family Law. The possession of minors as regulations requires a constitutional analysis, backed by international legislation, as well as in the Code of Children and Adolescents, complementary laws and comparative law, which allows analyzing the legal gaps that the Ecuadorian legal system presents, which evidently complicates that the ideal of justice and / or equity pursued by the judge comes to be fulfilled. Ecuador being a constitutional state of rights and justice, characterized by its social vision, as well as the defense of the family as a fundamental pillar of society requires a legal change in its current vision of tenure and parental rights, as it must be broken the paradigm of granting them only for a matter of social identity and gender, which historically fell to the mother of minors. From the sociological sphere, a divorce process is the failure of cohabitation between the spouses, which implies the rupture of a life project of the couple, with the aforementioned background, currently the Code of Childhood and Adolescence is still insufficient to resolve the existence of conflicts that could arise between the parents of minors, this with the purpose of being able to obtain possession or parental rights during the Litigation. This paper analyzes the effects of the separation of the parents and the restrictions that they impose in relation to the right of visits of the father who did not become a custodian, which leads the judge to decide on deep couple problems, which raises questions : the regime of visits, the role of the justice operator in cases of domestic violence, the role of minors before their parents during the judicial process.